Respuesta :
y = x^2 + 8x - 3
y = x^2 + 8x + (8/2)^2 - 3 - (8/2)^2
y = x^2 + 8x + 16 - 3 - 16
y = x^2 + 8x + (8/2)^2 - 3 - (8/2)^2
y = x^2 + 8x + 16 - 3 - 16
Answer:
The next step will be : [tex]x^{2}+8x+16-3-16[/tex].
Step-by-step explanation:
we are given a quadratic equation as:
[tex]y=x^2+8x-3[/tex]
now we have to find next step in the process for completing the square on the given quadratic
[tex]y=x^2+4^{2}+2\ \times x \times4-4^{2}-3[/tex]
[tex]y=x^2+8x+16-3-16[/tex]
Hence, the next step will be [tex]y=x^2+8x+16-3-16[/tex].